Effect of different diet methods on body composition and insulin, leptin, and ghrelin levels in overweight women - Begum Sarica; Gulbin RUDARLI NALCAKAN; Ece ONUR (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2022)
Introduction. This study aims to compare the effects of similar calorie-restricted intermittent overnight fasting diet (OFD) and frequent-meal diet (FMD) on body composition and insulin, leptin, and ghrelin levels in overweight women. Materials and Methods: While the FMD was administered as six mealtimes, the OFD was administered as five mealtimes and at least 12 hours overnight fasting for four weeks. Some parameters regarding the metabolic rate and fat metabo-lism (glucose, insulin, HOMA-IR, leptin, ghrelin levels), body composition, resting metabolic rate, and physical activity level were measured before and after the diet. Results: There was no sig-nificant difference in the resting metabolic rate (kcal) and fat-carbohydrate oxidation (g/min), while diet programs showed a similar significant improvement in body composition in both groups (p < 0.05). The glucose and insulin levels in OFD and the insulin level and the insulin re-sistance index in FMD significantly decreased (p < 0.05). There were significant differences in the leptin (-37%) and ghrelin (5.8%) levels in FMD, but only a significant decrease in the leptin level (-49%) was observed in OFD. Conclusions: After a 4-week same calorie-restricted FMD with six meals and OFD with a 12 hour-overnight fasting, similar improvements in the body composition and the insulin, leptin, and ghrelin levels have been achieved.